Infestation indices and characterization of injuries of Drosophila suzukii Matsumura (Diptera: Drosophilidae) in Barbados cherry - Louzeiro, Léo Rodrigo Ferreira; Souza-Filho, Miguel Francisco; Raga, Adalton; Bulgarelli, Carla A.; Klaczko, Louis Bernard (EntomoBrasilis, 2020)
Females of Drosophila suzukii Matsumura (Diptera: Drosophilidae) have a serrated ovipositor that causes severe physical damage to soft fruit. This behaviour results in the early ripening and accelerated rotting of infested fruit. In addition, feeding by larvae softens of the fruit peel, causing in a depreciation in commercial value. In this study, results of infestation indices, pupal viability, egg-adult period, degradation time of infested fruit, and description of physical injuries caused by oviposition and larval feeding of D. suzukii in Barbados cherries (Malpighia emarginata DC., Malpighiaceae) are described. Overall, our results and discussion contribute to the understanding of the status of D. suzukii as an insect pest of the Barbados cherry.